PENGARUH BIAYA DISTRIBUSI TERHADAP PENJUALAN DENGAN MEDIASI BIAYA PROMOSI PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Perdana, Aprin; Mayasari, Rosalina Pebrica; Arifin, Firmansyah (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
This study aims to analyse the effect of distribution costs on sales by mediating promotional costs. The population of this study is 14 automotive companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Research samples were taken using purposive sampling techniques so that as many as 8 companies were obtained. The type of data used in this study is secondary data obtained from financial statements and annual reports. The analysis technique used in this study used multiple linear regression analysis and Sobel test with the help of SPSS version 26. The results showed that 1) Distribution Costs have a significant effect on sales; 2) Promotional costs affect sales; 3) Distribution Costs affect Promotional Costs; and 4) Promotional Costs Mediate the Effect of Distribution Costs on Sales.